Analysis of Translation Techniques and Translation Procedures: Newmark’s and Molina & Albir’s Translation Frameworks - Gunawan Tambunsaribu (Darul Ilmi Bina Insan Foundation, 2026)
This study examines the conceptual similarities between Peter Newmark’s translation procedures and Molina and Albir’s translation techniques to determine the extent to which both frameworks share equivalent categories and theoretical orientations in explaining translation from the source language (SL) to the target language (TL). Employing a qualitative descriptive method with a comparative theoretical approach, the study analyzes and compares the classifications proposed by both scholars to identify corresponding categories, conceptual parallels, and functional similarities. The findings reveal substantial equivalence between the two frameworks, particularly in the categories of transference–borrowing, naturalization–naturalized borrowing, cultural equivalent–adaptation, descriptive equivalent–description, modulation–modulation, compensation–compensation, transposition–transposition, recognized translation–established equivalent, and through-translation/literal translation–literal translation/calque. Both models similarly emphasize meaning preservation, cultural adaptation, grammatical restructuring, equivalence, and target-language acceptability, despite differing in terminology and classification. These findings suggest that Newmark’s procedures and Molina and Albir’s techniques are complementary rather than competing frameworks. While Newmark provides a procedure-oriented perspective, Molina and Albir offer a more systematic operational classification of translation choices. Integrating both frameworks contributes to a more comprehensive understanding of translation processes and offers a stronger theoretical foundation for translation analysis, pedagogy, and practice.